Hubungan Produk Tahu dan Tempe dalam Optimalisasi Laba (Keuntungan Maksimum) pada UD Wahyu di Kota Denpasar - AHMAD MAULA ABIDIN; I WAYAN WIDYANTARA; I GUSTI AGUNG AYU AMBARAWATI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Relationship of Products Tofu and Tempeh for the Optimization of Profits(Maximum Profits) at UD Wahyu in Denpasar City UD Wahyu is one of the largest industry tofu and tempeh in Denpasar, proved by itsability of the average monthly production reached 167.36 tons of tofu and 51.76 tonsof tempeh. Problem faced by UD Wahyu is the selling price of tofu and tempehremain the same every year and uncertain incurred costs causing change profits overtime. The purposes of the research are to determine the production relationshipbetween tofu and tempeh and to find out the optimal production of tofu and tempehby UD Wahyu. Data collected by in-depth interview to the owner and observation tothe local site of production. Data analysis techniques was using regression andmaximum profit analysis by the marginal cost approach. The results showed thatproduction relationship between tofu and tempeh is complementary. It means thatany increase of tofu production will be followed by an increase in tempehproduction. The optimal monthly production of tofu amounted to 69.582 tons and theoptimal production of tempeh every month prevailed into two options, amounted to32.3073 tons and 43.9101 tons respectively. Profits earned by UD Wahyu fromproduction of 32.073 tons tempeh and 69.582 tons tofu between Rp 44.618.449 andRp 147.989.431. While profits earned by UD Wahyu production of tempeh 43.9101tons and tofu 69.582 tons between Rp 112.318.141 and Rp 215.689.123. Averageproduction of tofu and tempeh at UD Wahyu every month still exceeds the optimalproduction. To control costs, UD Wahyu is recommended to work on the optimalproduction.